Effect of Solow Variable To The Economic Growth in Southeast Asia - Soejoto, Ady; Cahyono, Hendry; Solikhah, Ni’matush (International Journal of Economics and Financial Issues, 2017)
Economic Growth in South East Asia is very dynamic and interesting. This paper aims to analyze the defining factor of that condition. This paper uses regression analysis to determine the impact of labor, investment, human resources, natural resources, and technology toward economic growth (Solow variable). The result indicates that Solow variable affect differently to each country. In Indonesia and Brunei, investment, human resources, and labor have significant effect toward economic growth. In Thailand and Philippines, investment, natural resources, and labor affect economic growth significantly. In Malaysia investment, technology, and human resources have significant effect toward economic growth. In Vietnam, technology, natural resources, human resources, and labor affect economic growth significantly. Meanwhile, In Cambodia technology, natural resources, and labor have significant impact toward economic growth. Keywords: investment, human resources, natural resources, technology, labor, economic growth. JEL Classifications: O0, O4